2019
DOI: 10.3390/rs11060649
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Carbon Fluxes from Eddy Covariance Data and Satellite-Derived Vegetation Indices in a Karst Grassland (Podgorski Kras, Slovenia)

Abstract: The Eddy Covariance method (EC) is widely used for measuring carbon (C) and energy fluxes at high frequency between the atmosphere and the ecosystem, but has some methodological limitations and a spatial restriction to an area, called a footprint. Remotely sensed information is usually used in combination with eddy covariance data in order to estimate C fluxes over larger areas. In fact, spectral vegetation indices derived from available satellite data can be combined with EC measurements to estimate C fluxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 59 publications
2
14
0
Order By: Relevance
“…Among the five VI explored for estimating GPP and NEE in the present study, EVI was found to be the best VI proxy for both GPP and NEE. This seems adequate since the ecosystem addressed is not a pure grassland as it was the case in a previous study where NDVI was the best proxy for GPP [ 11 ]. The heterogeneous nature of the ecosystem in this study, made of a mix of tree patches and grassland, partly explains why EVI performed better than NDVI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among the five VI explored for estimating GPP and NEE in the present study, EVI was found to be the best VI proxy for both GPP and NEE. This seems adequate since the ecosystem addressed is not a pure grassland as it was the case in a previous study where NDVI was the best proxy for GPP [ 11 ]. The heterogeneous nature of the ecosystem in this study, made of a mix of tree patches and grassland, partly explains why EVI performed better than NDVI.…”
Section: Discussionmentioning
confidence: 99%
“…The mean annual temperature is 10.5˚C, and the average annual precipitation is about 1370 mm. These are statistics of 30 years (1971-2000) climate data from four different meteorological stations of the area [11,19]. The study area (Fig 1) covers a diverse ecosystem where both grass, shrubs and tree patches coexist.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…Verification activities can be carried out on multiple spatial and temporal scales and include data from standard computational inventory methods, instrumental methods, remote sensing and modeling. All information must be processed by a hybrid data center system [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%